ANALISIS FAKTOR KESULITAN BELAJAR IPA SISWA KELAS V SDN 61 MARIO KECAMATAN PONRANG KABUPATEN LUWU - Nurasia; Erni; Eva Sohriati (Universitas Cokroaminoto Palopo, 2023)
The purpose of this research is to analyze the level of students' learning difficulties in learning science. The type of research is qualitative research. The subjects in this study were 19 students in class V at SDN 61 Mario, Ponrang District, Luwu Regency. Data collection techniques in this research is questionnaires. The research instrument used was a questionnaire on students' natural science learning difficulties which consisted of 30 questions. The data analysis technique used was data reduction, data presentation, and drawing conclusions. The results of this study indicated that the results of the questionnaire analysis on the difficulty factor of learning science for indicators of learning motivation were 65.66%, Interest was 62.87%, Attitude was 60.96%, school environment by 59.90% and family environment by 66.42%.